Uncovering the Values of Balinese Local Wisdom in Household Accounting Practices of Tenant Farmers - Eka Putri Suryantari; Ni Putu Erviani Astari (Politeknik Ganesha Medan, 2026)
Previous research has not specifically mapped household accounting practices among tenant farmers in the Subak system, nor derived the value of Balinese local wisdom into operational principles of budgeting, recording, and accountability practices in household financial management. This study aims to identify household accounting practices carried out by tenant farmers in Subak Umadesa and to formulate conceptual propositions regarding the relationship between the values of Tri Hita Karana (THK), pade gelahang, and pang pade payu with budgeting, recording, and household financial accountability practices. The study employs a qualitative approach using the transcendental phenomenology method through field observation, in-depth interviews, and documentation of three tenant farmer informants. The results indicate that farmers have implemented financial planning practices, simple recording, and trust-based debt management, although these have not yet been accompanied by formal reporting and systematic financial performance evaluation. This study produces a conceptual framework that positions THK values as the basis for ecologically harmonious budgeting decision-making (palemahan), the value of pade gelahang as a principle of collective accountability in debt and capital management, and the value of pang pade payu as the foundation of transparency in trust-based recording practices. The limited number of informants (three participants) restricts the generalizability of the findings, so the output of this study is positioned as contextual conceptual propositions in the household accounting practices of tenant farmers.